PRELIMINARY STUDY OF FISH CULTURE IN ABANDONED SAND MINING POOL - Bambang Gunadi; Lukas Dharma; Ikhsan Khasani; Yosmaniar Yosmaniar; Lies Setijaningsih (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
One of main problems in freshwater aquaculture development in Indonesia, especially in Java, is unavailability of developing zone. It is important to find an underutilized area that meets for industrial scale freshwater aquaculture, i.e. sufficient water supply, wide area, and located in one area or zone. The abandoned mining (sand, tin, etc.) pools distributed along the country might be the potential area for freshwater aquaculture business. For example, there are at least 13 water pools with total surface area of 250 ha at 15 km side of Citarum River in Karawang District (West Java Province). This study was conducted to obtain preliminary data about the prospect and potency of fish culture (tilapia, clariid catfish, and ‘patin’ catfish) in abandoned sand-mining pools in Karawang District. Mini floating net cages of 1 x 1 x 1.5 m3 size were used for culturing fish, i.e. patin catfish (Pangasianodon hypophthalmus), nile tilapia (Oreochromis niloticus), and clariid catfish (Clarias gariepinus), separately. Patin catfish were stocked at a size of 2 g with a density of 300 fish per cage, tilapia were stocked at a size of 6 g with a density of 400 fish per cage, while the clariid catfish were stocked at a size of 1.4 g with a density of 980 fish per cage. A floating commercial feed (30%—32% protein, 3%—5% fat) was used at a daily rate of 9% biomass weight at the beginning and reduced gradually to 3% at the final culture period. Observed data showed that patin catfish grew from the initial size of 2.08 g to the final size 299.59 g in 5 months, nile tilapia grew from individual initial size of 5.92 g to the final size of 247.12 g in 14 weeks, and clariid catfish grew from initial size of 1.39 g to the final size of 73.10 g in 8 weeks. These three species were technically prospective for aquaculture development in the abandoned sand-mining pools.